Java project on periodontal diseases: the relationship between vitamin C and the severity of periodontitis - Amaliya (Blackwell Synergy, 2007)
Objective: To study the relationship between vitamin C and the severity of periodontitis. Material and Methods: The study population consisted of subjects from the Malabar/ Purbasari tea estate on West Java, Indonesia. In 2002, clinical measurements were performed in 128 subjects, including evaluation of plaque, bleeding on probing, pocket depth and attachment loss. In 2005, 123 out of 128 subjects could be retrieved who were present at the examination of 2002. Blood samples were taken to measure plasma vitamin C levels. Information about the subject’s dietary habit was obtained by means of a personal interview guided by a questionnaire. Results: Plasma levels of vitamin C ranged from 0.02 to 34.45 mg/l with a mean of 7.90 mg/l ( 5.35). The correlation coefficient between plasma vitamin C level and periodontal attachment loss was 0.199 (po0.05); stepwise linear regression revealed that vitamin C levels explained 3.9% of the variance in periodontal attachment loss. Subjects with vitamin C deficiency (14.7% of the study population) had more attachment loss compared with those with depletion or normal plasma vitamin C values. Conclusion: The negative association between plasma vitamin C levels and periodontal attachment loss suggests that vitamin C deficiency may contribute to the severity of periodontal breakdown.